Community-Based Research in Culinary Tourism: The Case of the International Fried Duck Festival Kartasura - Rohimat, Asep Maulana; Arifin, Mohammad Rahmawan; Piliyanti, Indah; Ali, Ichsanul Ibad; Mahmudulhasan, Mahmudulhasan (BISNIS, 2025)
This study explores the development of Kartasura as a culinary tourism destination through the 2023 International Fried Duck Festival, using a Community-Based Participatory Research (CBPR) approach. The festival emerged from the collaboration between FEBI UIN Raden Mas Said, the Kartasura District Government, the Pawartos community, and the Fried Duck Vendors Association. CBPR methodology facilitated active participation of stakeholders throughout the planning and implementation stages. The findings reveal that the festival successfully engaged local SMEs, distributed 3,000 free portions of fried duck rice, and introduced Kartasura’s culinary identity to an international audience, including representatives from five countries. Nevertheless, the study highlights a critical limitation in terms of sustainability, as the festival has not yet evolved into an annual agenda. More sustainable practices are observed in routine events such as Kartasura’s Car Free Day and the Ambal Warsa Kartasura anniversary celebration. These findings underscore the need for strategic integration and continuous evaluation to strengthen Kartasura’s position as an emerging international culinary destination.